PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIK SISWA SMP MELALUI METODE PENEMUAN TERBIMBING BERBANTUAN SOFTWARE GEOGEBRA - Annajmi Annajmi (MES: Journal of Mathematics Education and Science, 2016)
AbstractThis research is aimed to know: 1) the increasing of student’s understanding concepts mathematics ability as an impact of guided discovery method on learning with Geogebra software, 2) the interaction between learning and  early mathematic ability  in increasing understanding concepts mathematics ability, and 3) The student’s activities  in teaching and learning. This research was a quasy experiment with the sample of this research was 80 students, consisted of VII-1 class with 40 students as an experiment 1 class and VII- class with 40 students as a experiment 2  class. The instruments used consist of understanding concepts ability test and the observation sheets. The data analyzed by using anacova in the SPSS program. Based on the result of this research, it could be concluded that the  improvement of student’s understanding concepts mathematics ability through guided discovery method with Geogebra software was better than improvement of student’s understanding concepts mathematics ability without Geogebra software. There was not an interaction between the instructional approach and early mathematic ability to improvement of student’s understanding concepts mathematics ability. Students activity in learning by using guided discovery method with software Geogebra was better than students activity without Geogebra software. Keywordguided discovey, geogebra software, the ability of understanding mathematical concepts